The Reformed conceptualisation of morality - Vosloo, Robert (Verbum et ecclesia, 2023)
This article distinguishes, on the one hand, between the characteristic features of Reformed ethics and Reformed conceptualisations of morality on the other. With this distinction in mind, the article first highlights - by drawing on the work of some contemporary Reformed theologians and their interpretation of some key figures and texts from this tradition - the centrality of categories such as belonging, gratitude, the law and holiness for a Reformed understanding of ethics. This discussion opens a window onto some features related to the conceptualisation (or conceptualisations) of morality in the Reformed tradition. Intradisciplinary and/or interdisciplinary implications: The article emphasises four aspects in this regard, namely that Reformed ethics is grounded in faith and doctrine, that ethics and the practical Christian life belong at the heart of the Reformed faith, that Reformed ethics is an ethics of freedom and that the theological logic of the Reformed tradition implies a deeply historical and contextual vision.